2016
DOI: 10.1111/bjh.14277
|View full text |Cite
|
Sign up to set email alerts
|

Assessing cardiac and liver iron overload in chronically transfused patients with sickle cell disease

Abstract: Transfusional iron overload represents a substantial challenge in the management of patients with sickle cell disease (SCD) who receive chronic or episodic red blood cell transfusions. Iron-induced cardiomyopathy is a leading cause of death in other chronically transfused populations but rarely seen in SCD. Study objectives were to: (i) examine the extent of myocardial and hepatic siderosis using magnetic resonance imaging (MRI) in chronically transfused SCD patients, and (ii) evaluate the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
18
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 74 publications
7
18
1
1
Order By: Relevance
“…A recent study reported 32 children with SCD undergoing chronic transfusion therapy who did not develop evidence of significant cardiac iron overload . However, in the two adult patients that we present, we show that ongoing transfusions can lead to significant cardiac damage.…”
Section: Discussioncontrasting
confidence: 44%
“…A recent study reported 32 children with SCD undergoing chronic transfusion therapy who did not develop evidence of significant cardiac iron overload . However, in the two adult patients that we present, we show that ongoing transfusions can lead to significant cardiac damage.…”
Section: Discussioncontrasting
confidence: 44%
“…Although iron-related cardiac morbidity is generally absent in patients with SCA, iron overload is still associated with several morbidities including pain crisis, high hospitalization rates, end-organ damage as well as mortality. [6][7][8][9][10] The effect of higher dosing was evident in our study. Although patients were given higher deferasirox doses when they had higher baseline serum ferritin levels, mean values usually remained below30 mg/kg/d even in patients with serum ferritin levels >2500 μg/L at baseline.…”
Section: Discussionsupporting
confidence: 60%
“…Our study has also observed a considerable increase in the proportion of patients with serum ferritin levels <1000 μg/L from baseline to end of study, thus, potentially giving patients the opportunity of more favorable future outcomes. Although iron‐related cardiac morbidity is generally absent in patients with SCA, iron overload is still associated with several morbidities including pain crisis, high hospitalization rates, end‐organ damage as well as mortality …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations